Engaging citizen scientists: designing an open research system for collaborative problem exploration - Michael Gau; Anke Greif-Winzrieth; Alexander Maedche; Christof Weinhardt; Jan vom Brocke (Electronic Markets, 2025)
Open Science aims to make scientific research and its dissemination accessible to all levels of society to foster openness and transparency. Engaging in a dialogue with society to explore real-world problems is particularly important to increase the relevance of information systems research. However, reaching out to citizens and engaging them in the research problem exploration process on a large scale is challenging for researchers. In this research, we build on existing prescriptive knowledge and design an open research system to involve citizens in the problem exploration process. Applying the design science research methodology, we report on the results and findings of one complete design cycle. We deliver design knowledge including (1) design requirements derived from the literature, (2) propose a set of design principles, (3) an instantiation of the design principles in the form of design features as well as a publicly available artifact, and (4) evaluations through a series of online experiments and two field studies with actual citizens. With this research project, we contribute design knowledge for the class of citizen science systems and present an approach and a publicly available instantiation that can be leveraged for open research problem exploration to engage with society members at large.
Keywords: O36; 620; Research problem exploration; Open science; Citizen science; Design science research; Design principles